Activity-dependent expression of neuronal PAS domain-containing protein 4 (npas4a) in the developing zebrafish brain - Klarić, Thomas; Lardelli, Michael; Key, Brian; Koblar, Simon; Lewis, Martin (Frontiers in Neuroanatomy, 2014)
In rodents, the Npas4 gene has recently been identified as being an important regulator of synaptic plasticity and memory. Homologs of Npas4 have been found in invertebrate species though their functions appear to be too divergent for them to be studied as a proxy for the mammalian proteins. The aim of this study, therefore, was to ascertain the suitability of the zebrafish as a model organism for investigating the function of Npas4 genes. We show here that the expression and regulation of the zebrafish Npas4 gene, npas4a, is remarkably similar to that of the rodent Npas4 homologs. As in mammals, expression of the zebrafish npas4a gene is restricted to the brain where it is up-regulated in response to neuronal activity. Furthermore, we also show that knockdown of npas4a during embryonic development results in a number of forebrain-specific defects including increased apoptosis and misexpression of the forebrain marker genes dlx1a and shha. Our work demonstrates that the zebrafish is a suitable model organism for investigating the role of the npas4a gene and one that is likely to provide valuable insights into the function of the mammalian homologs. Furthermore, our findings highlight a potential role for npas4a in forebrain development.